"To read the signs of the time": Ukrainian baptist theology in light of the social transformations challenges in Ukraine and the russian-Ukrainian war - Tregub, Ganna Anatoliivna (Ukrai͏̈ns'ke relihijeznavstvo, 2017)
This article describes present day reaction of Ukrainian Baptist community on the current geopolitical situation in Ukraine and its reflection in first modern independent theological steps of named Late Protestant denomination. It is stressed, that complete process of theology creation is a maker of healthy and protected, factually free religious life in certain boundaries of country or land. Also it’s shown that in Ukrainian case for present day’s start of the modern Baptist theology discourse the trigger factor was Revolution of dignity 2013-2014 and de-facto Russian-Ukrainian ongoing war. Ideas and practices raising up in their environment mark how all this impacts the whole Ukrainians and members of Ukrainian Baptist Churches, do they feel themselves as responsible citizens of their country, would they react or not on realities of their country life or not, and do they think about question of their identity (Ukrainian Baptists of Baptists in Ukraine). This entire things signal about deeper processes of final institutionalization of named denomination, its entry into democratic era together with state.